Penerapan Continuous Review System dan Simulasi Monte Carlo untuk Meminimumkan Stockout Bahan Baku di CV. XYZ - Jefry Pradana Kusuma Azhary; Siti Mundari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
CV. XYZ is a manufacturing company producing electrical distribution pole accessory components operating a make-to-stock production system. A reactive, non-data-driven inventory control system caused four stockout incidents for UNP10 iron bars and strip plates during February 2025–January 2026, forcing costly emergency orders. This study aims to determine optimal safety stock, reorder point, and order quantity using the Continuous Review System (CRS) Hadley-Within Model, validated through Monte Carlo Simulation across 12 demand scenarios. Forecasting was conducted using Weighted Moving Average for UNP10 iron bars and Moving Average for strip plates. Results show CRS implementation reduced total inventory costs from IDR 20,612,890 to IDR 12,658,456 per year, achieving 38.59% efficiency, with policies proven stable against demand fluctuations.